The Makhweyane bow of Swaziland: music, poetics and place - Stacey, Cara L (College of Music, 2018)
This dissertation investigates how the contemporary performers of the Swazi gourd-resonated bow, the makhweyane, create music. Since David Rycroft's study of Swazi bow music in the 1960s and 1970s, little study has been devoted to this musical instrument. The makhweyane is played by a handful of people, each appearing to consider him or herself the last bearer of this tradition. Despite this, however, musical bows have been co-opted as icons of Swazi national identity, and, along with the Incwala (the "first fruits" festival) and Umhlanga ("reed dance") ceremonies, are used as public affirmation of Swazi cultural homogeneity to rally support for the monarchy. The research investigates how musicians create new music for this single-stringed instrument. It also explores, through oral testimony, musical analysis, and practice-based methodologies, the discourse surrounding composition and musical innovation on this rare instrument. Players learn and create through both solitary and participatory exploration and music-making. This research explores how current makhweyane music can be read as oral testimony with regards to the lives of musicians, but also how diverse current praxis serves many functions: as "radio" for lone travelers, as comfort for broken hearts, and as individual acts of citizenry within a broader national environment. This dissertation explores the musical, technical, and social parameters engaged when creating new repertory - the myriad invisible spectres to whom players play and for whom players compose - and the shape that new, resilient makhweyane sounds are taking. It extends David Rycroft's musicological analysis of the 1960s and 1970s to include an investigation into current dialectics between individual notions of creative innovation and musical memory, and the national cultural imaginary. My findings suggest a reframing of 'traditional' musicians from elderly 'culture-bearers' to responsive, innovators and active contemporary musicians, along with their urban-based, younger counterparts. Opening with the King's call for new compositions to be created, this dissertation reads the makhweyane as a prism for Swaziness, for learning and storytelling, for the imagination and remembering, and for creation.